Radiative Heat and Mass Transfer of an MHD Free Convection Flow Along a Stretching Sheet with Chemical Reaction, Heat Generation and Viscous Dissipation - Zahan, Ishrat; Samad, MA (Dhaka University Journal of Science, 2013)
In the present study, an analysis is carried out to investigate the effect of chemical reaction and radiation on a steady two-dimensional magneto-hydrodynamics (MHD) heat and mass transfer free convection flow of a viscous incompressible fluid along a stretching sheet with heat generation along with the effect of viscous dissipation. The basic non-linear partial differential equations governing the flow field are reduced to a system of coupled non-linear ordinary differential equations by similarity transformations and the equations are solved numerically by applying Nachtsheim-Swigert shooting iteration technique along with sixth order Runge-Kutta integration scheme. The numerical results with respect to embedded parameters are displayed graphically for the non-dimensional velocity, temperature and concentration profiles. Finally the effects of the pertinent parameters which are of physical and engineering interest are presented in tabular form. Dhaka Univ. J. Sci. 61(1): 27-34, 2013 (January) DOI: http://dx.doi.org/10.3329/dujs.v61i1.15092